Developing Local Potential Through Training On Making Presto Milkfish At PKBM Arrahman, Talabiu Village, Woha District, Bima Regency - Hendra, Hendra; Asmiatiningsih, Sri; Akbar, Putra Chairil; Rusli, Rusli; Iptidaiyah, Muhamad; Taufiq, Muhammad; Arman, Arman; Rijal, Muhammad Nur; Oktafiana, Pingkan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community service program aims to enhance the skills and economic independence of the residents of Talabiu Village Woha District Bima Regency, through training in the production of soft-boned bandeng presto (pressure-cooked milkfish). Talabiu Village has significant potential in milkfish cultivation; however, the added value of its products remains low due to limited post-harvest processing. The training was organized by PKBM Arrahman in collaboration with the Directorate of Courses and Training, Directorate General of Vocational Education, Ministry of Education, Culture, Research, and Technology, from July 1 to 20, 2025. The implementation methods included socialization, participatory training, mentoring, monitoring, and evaluation. The training materials covered the potential of milkfish resources, the bandeng presto production process, sanitation and hygiene practices, packaging techniques, and basic marketing strategies. The results show that participants successfully completed all stages of the production process and produced bandeng presto with good organoleptic qualities (taste, aroma, and texture). This activity had a positive impact on improving participants’ technical skills, entrepreneurial mindset, and the economic value of local fishery products. It is expected that this program will continue through independent production and the development of small-scale milkfish processing enterprises within the community.